Pollens in bee-breads as an indicator of honey sources (Bangladesh Journal of Scientific and Industrial Research, 2014)
Adulteration of honey and bee-breads in the markets are becoming a matter of deep corncern. The aim of this study, therefore, is to authenticate the natural sources of the honey and bee breads produced by the University of Ilorin Apiary Farm and Jatropha Plantation. A microscopic survey of some pollen breads collected from the Apiary Farm of 6 colonies and Jatropha Plantation of one colony at the University of Ilorin, Ilorin, Nigeria revealed the presence of 9 types of pollens in honey-breads or bee-breads produced by the bees in the area under study. These pollen types include monoporate, salcate, triporate, tricolpate, pericolpate, panporate, biporate, salcate and vesculate. Monorate, colpate, triporate and panporate pollen types are the most frequent occuring in all colonies, followed by salcate, biporate and tricolpate. The least frequent types are pericolpate and vesculate pollens occuring only in the colony A. Density of each of these pollens were also determined in each colony. Some impurities were detected in colonies B, C and E. Panporate pollen of Jatropha curcas is of high frequency in the colony of Jatropha indicating that honeybees visit the Jatropha plants more frequently. So, the honey from the plantation might contain high percentage of panporate pollens. The honey produced at the Apiary and Jatropha Plantation at the University of Ilorin, Ilorin, Nigeria is based on this study. A polyfloral or multifloral type rather than unifloral or monofloral because it contains many types of pollen indicating its source from more than one plant sources or more than one nectars of different entomophilous plants exhibiting the presence of some anemophilous pollens. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.16966 Bangladesh J. Sci. Ind. Res. 48(4), 247-252, 2013